EVALUASI REAKSI PASAR ATAS DEPRESIASI NILAI TUKAR RUPIAH AKIBAT PANDEMI COVID-19 - Anggreni, Diah; Putri, I Gusti Ayu Made Asri Dwija; Suartana, I Wayan; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022DO - 10.24843/EEB.2022.v11.i11.p01, 2022)
This research was conducted on public companies listed on the Indonesia Stock Exchange (IDX), and the population in this study were all publicly traded companies listed on the Indonesia Stock Exchange. The sample in this study are companies that are members of the IDX-80 index. Data collection was carried out using the websites www.web.idx.id and www.financeyahoo.com. The sampling method used in this study is non-probability sampling with purposive sampling technique. The data analysis technique used is paired sample t-test. The results of the analysis show that there are differences in Cumulative Abnormal Return (CAR) and trading volume activity (TVA) in companies before and after the depreciation of the rupiah exchange rate in 2020. The implications of this research include two things, namely theoretical implications and practical implications. Theoretical implications relate to the contribution of the study to cumulative abnormal returns and the average trading volume activity before and after the depreciation of the rupiah against the US dollar. The practical implications relate to research contributions to public companies listed on the Indonesia Stock Exchange (IDX), especially companies that are members of the IDX-80 index.